Joint Group and Multi Institutional Position Opinion: Cirrhotic Cardiomyopathy—From Fundamentals to Applied Tactics - Ivan Rankovic; Ivana Babic; Jelena Martinov Nestorov; Jelena Bogdanovic; Maja Stojanovic; Jovanka Trifunovic; Nikola Panic; Mihailo Bezmarevic; Jelena Jevtovic; Dusan Micic; Vladimir Dedovic; Nemanja Djuricic; et al. (Medicina)
Cirrhotic cardiomyopathy (CCM) is a diagnostic entity defined as cardiac dysfunction (diastolic and/or systolic) in patients with liver cirrhosis, in the absence of overt cardiac disorder. Pathogenically, CCM stems from a combination of systemic and local hepatic factors that, through hemodynamic and neurohormonal changes, affect the balance of cardiac function and lead to its remodeling. Vascular changes in cirrhosis, mostly driven by portal hypertension, splanchnic vasodilatation, and increased cardiac output alongside maladaptively upregulated feedback systems, lead to fluid accumulation, venostasis, and cardiac dysfunction. Autocrine and endocrine proinflammatory cytokines (TNF-alpha, IL-6), as well as systemic endotoxemia stemming from impaired intestinal permeability, contribute to myocardial remodeling and fibrosis, which further compromise the contractility and relaxation of the heart. Additionally, relative adrenal insufficiency is often present in cirrhosis, further potentiating cardiac dysfunction, ultimately leading to the development of CCM. Considering its subclinical course, CCM diagnosis remains challenging. It relies mostly on stress echocardiography or advanced imaging techniques such as speckle-tracking echocardiography. Currently, there is no specific treatment for CCM, as it vastly overlaps with the treatment of heart failure. Diuretics play a central role. The role of non-selective beta-blockers in treating portal hypertension is established; however, their role in CCM remains somewhat controversial as their effect on prognosis is unclear. However, our group still advocates them as essential tools in optimizing the neurohumoral pathologic axis that perpetuates CCM. Other targeted therapies with direct anti-inflammatory and antioxidative effects still lack sufficient evidence for wide approval. This is not only a review but also a comprehensive distillation of the insights from practicing clinical hepatologists and other specialties engaged in advanced approaches to treating liver disease and its sequelae.